2020
DOI: 10.1002/ejoc.202000056
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]Fluoroform with High Molar Activity

Abstract: Fluoroform is an interesting motif for the isotopologue labelling of biologically active compounds with fluorine‐18 for PET imaging. However, so far the building block [18F]fluoroform and consequently the [18F]trifluoromethylated products suffered from low molar activities ranging from 0.1 to 30 GBq/µmol due to isotopic dilution under the strongly basic standard radiofluorination conditions. In this article the synthesis of high molar activity [18F]fluoroform is described. By implementing a recently reported n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 19 publications
(33 reference statements)
2
40
1
Order By: Relevance
“…It is worth noting that radiolabeling a trifluoromethyl group, such as those contained in compound 65 , has been traditionally difficult due to isotopic dilution with fluorine-19. However, methods including using a novel radiofluorination reagent and reduction of base-cryptand concentration have been developed, through which one fluorine-18 is introduced into the molecule [ 85 ]. Other compounds may be used as a reference in developing new PET tracers, such as compounds 72 and 74 , which exhibited excellent to moderate IC 50 values, specificity for GPR44, preferable plasma clearance, and favorable bioavailability.…”
Section: Ramatroban-based Analogues For Potential Gpr44 Bindingmentioning
confidence: 99%
“…It is worth noting that radiolabeling a trifluoromethyl group, such as those contained in compound 65 , has been traditionally difficult due to isotopic dilution with fluorine-19. However, methods including using a novel radiofluorination reagent and reduction of base-cryptand concentration have been developed, through which one fluorine-18 is introduced into the molecule [ 85 ]. Other compounds may be used as a reference in developing new PET tracers, such as compounds 72 and 74 , which exhibited excellent to moderate IC 50 values, specificity for GPR44, preferable plasma clearance, and favorable bioavailability.…”
Section: Ramatroban-based Analogues For Potential Gpr44 Bindingmentioning
confidence: 99%
“…11 In addition, a study of producing [ 18 F]uoroform with increased A m has been reported, based on the strategy using [ 18 F]triyl uoride under less basic condition to reduce the decomposition of diuoroiodomethane (A m ¼ 97 AE 20 GBq mmol À1 (n ¼ 3)). 12 In 2013, we reported that the triazolium group of 1,2,3-triazolium triate functioned as a very good nucleofuge for displacement by the uoride ion. 13 The experimental conditions of this method were so mild that it could be used for the preparation of PET radiopharmaceuticals bearing O-[ 18 F] uoromethyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic [ 18 F]trifluoromethylation is well established and multiple strategies have been reported. [14][15][16][17][18] However, the reported methodologies mainly rely on [ 18 F]fluoroform as [ 18 F]trifluoromethylation agent. In organic chemistry, not many trifluoromethylation procedures report the use of [ 19 F]fluoroform, as alternative trifluoromethylation agents are generally preferred.…”
mentioning
confidence: 99%
“…One of the most applied nucleophilic trifluoromethylation agents is the Ruppert-Prakash reagent (Me 3 SiCF 3 ). 9 It was first described in 1984 by Ruppert et al 19 and found its first application in 1989 by Prakash et al 20 We therefore envisioned that developing a synthesis strategy for 18 F-labelled Ruppert-Prakash reagent would be very useful for the translation of CF 3 functionalization reactions that have been developed in fluorine-19 chemistry to radiofluorination reactions and PET tracer synthesis. 21 To synthesize [ 18 F]Me 3 SiCF 3 we followed a procedure reported by Prakash et al that reacted fluoroform with trimethylsilyl chloride in presence of potassium hexamethyldisilazide (KHMDS) as the base in toluene.…”
mentioning
confidence: 99%
See 1 more Smart Citation